Hur påverkar förtätningen stadens grönstruktur? - Jonsson, Karin (2009)
Urban density is not new, but rather one side of the continous processes of change underway in the city. During the urbanizing boom of the industrialization, when the cities grew bigger, the first spaces to be built on were vacant and planted areas in the interior of the district. The gardens that once were there were replaced by yardhouses. The idea of urban density is that a dense city means less distance between residential areas and workplaces, resulting in fewer shipments and travelers, which ultimately leads to lower energy consumption and lower emissions. Urban density may lead to shorter distances, but not necessarily.